Association between Aspartate Aminotransferase to Platelet Ratio Index with Sepsis-Associated Liver Injury and Outcome in Children - Manoppo, Jeanette Irene Christiene; Ipardjo, Angelica; Masloman, Nurhayati; Lang, Fima Lanra Fredrik G. (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Sepsis-associated liver injury (SALI) is among the major clinical characteristics of pediatric septicemia, and it is a distinct risk factor for multiorgan impairment and a high rate of death. The prompt identification and treatment of SALI in patients with septic conditions is critical. AIM: We aimed to discover the relationship between aspartate aminotransferase to platelet ratio index (APRI) and Sepsis-associated liver injury (SALI) as an early predictor. METHODS: Analytical observational study with a prospective cohort approach with primary data taken from 49 samples. Further, these results were analyzed to determine the relationship between the occurrence of SALI and laboratory results. RESULTS: The results of the analysis conducted from 49 samples, 23 people (46.9%) had SALI, and 22 people (44.9%) died. The median length of stay in the pediatric intensive care unit (PICU) was 9 days (interquartile range = 6.5–12.5). Significant relationship between aspartate aminotransferase to platelet ratio index (APRI) and the incidence of SALI with odds ratio (95% confidence interval) 2.32 (1.21: 4.44) and p = 0.011. The higher the APRI value, the longer the stay in the PICU. The correlation value (r) is 0.348 or low correlation CONCLUSION: There was a significant relationship between the APRI and sepsis-related liver injury as well as sepsis outcomes such as PICU length of stay and mortality. Increases in the APRI increase the risk of sepsis-related liver injury, mortality, and PICU length of stay.